Management of US men, women, and children with hemophilia and methods and demographics of the Bridging Hemophilia B Experiences, Results and Opportunities into Solutions (B‐HERO‐S) study. (April 2017) - Buckner, Tyler W.; Witkop, Michelle; Guelcher, Christine; Frey, Mary Jane; Hunter, Susan; Peltier, Skye; Recht, Michael; Walsh, Christopher; Kessler, Craig M.; Owens, Wendy; Clark, David B.; Frick, Neil; et al.
Abstract: The Bridging Hemophilia B Experiences, Results and Opportunities Into Solutions (B‐HERO‐S) initiative was launched in an effort to address specific gaps in the understanding of the psychosocial impact of mild‐moderate‐severe hemophilia B. The original Hemophilia Experiences, Results and Opportunities (HERO) qualitative study evaluated the needs of people with hemophilia A or B in multiple countries; however, a majority of participants had the more common moderate‐severe hemophilia A. The B‐HERO‐S study was designed in collaboration with the hemophilia community to evaluate the needs of adults with hemophilia B and caregivers of children with hemophilia B, including affected women and caregivers of girls with hemophilia. The report presented here describes participant demographics and comorbidities, as well as treatment regimens and access to treatment. Bleeding symptoms were reported by 27% of mothers of children with hemophilia B who participated. Women were more likely than men to self‐report arthritis and depression/anxiety as comorbidities associated with hemophilia B. More adults and children with hemophilia B were on routine treatment than on on‐demand treatment, and a high percentage of adults with moderate hemophilia B received routine treatment (86%). Many adults with hemophilia B (78%) and caregivers (69%) expressed concern about access to factor in the next 5 years, and of adults with hemophilia B, women more commonly experienced issues with access to factor in the past than did men (72% vs 44%). The findings of the B‐HERO‐S study reveal potential unmet needs of some patients with mild‐moderate hemophilia B, and the results may be leveraged to inform patient outreach by hemophilia treatment centers and education initiatives.